2021
DOI: 10.1155/2021/1097046
|View full text |Cite
|
Sign up to set email alerts
|

Application of Gabor Image Recognition Technology in Intelligent Clothing Design

Abstract: Aiming at the complex problem of image recognition feature extraction, this paper proposes an intelligent clothing design model based on parallel Gabor image feature extraction algorithm. Based on the intelligent parallel mode, the algorithm decomposes and merges the calculation process of the image Gabor transformation, decomposes the entire image Gabor feature extraction calculation process into a parallel part and a nonparallel part, and accelerates the parallel part by using multiple cores. The calculation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…By reviewing and analyzing the application of modern graphic design and traditional art design elements in the context of multiple integrations, the paper shows that combining modern graphic design and traditional art design elements can bring a more unique and novel visual experience to design works and at the same time can highlight the cultural connotation and artistic value of the works. In the literature [12], Gabor image recognition technology can achieve intelligent recognition and design of garment patterns, bringing a more convenient and efficient method to the garment design industry. The paper reviewed and analyzed the application of Gabor image recognition technology in intelligent garment design, and the research results showed that the use of Gabor image recognition technology could provide more accurate and comprehensive recognition and analysis of garment patterns, as well as more diverse and innovative design solutions and inspiration for garment designers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…By reviewing and analyzing the application of modern graphic design and traditional art design elements in the context of multiple integrations, the paper shows that combining modern graphic design and traditional art design elements can bring a more unique and novel visual experience to design works and at the same time can highlight the cultural connotation and artistic value of the works. In the literature [12], Gabor image recognition technology can achieve intelligent recognition and design of garment patterns, bringing a more convenient and efficient method to the garment design industry. The paper reviewed and analyzed the application of Gabor image recognition technology in intelligent garment design, and the research results showed that the use of Gabor image recognition technology could provide more accurate and comprehensive recognition and analysis of garment patterns, as well as more diverse and innovative design solutions and inspiration for garment designers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Qiao, S et al for the apparel design modeling in image feature recognition extraction, proposed an integrated parallel extraction method. The efficiency of image feature extraction in the apparel design model is improved by the acceleration effect of multi-core acceleration [14]. Xu, Q et al used the interactive output method to explore the role of non-heritage cultural elements and traditional crafts in modern clothing design, combined with experiments to prove that the fusion of cultural elements and clothing design can bring about a new design level [15].…”
Section: Introductionmentioning
confidence: 99%
“…Literature [12], in order to optimize the empowerment of traditional cultural elements in clothing brands, proposes that clothing brand designers should deeply understand the connotation of conventional culture and then connect traditional cultural elements and brands to promote the harmonious interaction between users and brands and traditional culture. Literature [13] conceived a clothing design framework with a parallel Gabor image feature extraction algorithm as the core logic. It tested it through experiments, verifying that the modified design framework can have a good effect on clothing fabric recognition.…”
Section: Introductionmentioning
confidence: 99%